Peripheral immune reactions following human traumatic spinal cord injury: the interplay of immune activation and suppression - Coenen, Hanne; Somers, Veerle; Fraussen, Judith (Frontiers in Immunology, 2024)
Traumatic spinal cord injury (SCI) damages the nerve tissue of the spinal cord, resulting in loss of motor and/or sensory functions at and below the injury level. SCI provokes a long-lasting immune response that extends beyond the spinal cord and induces changes in the composition and function of the peripheral immune system. Seemingly contradictory findings have been observed, as both systemic immune activation, including inflammation and autoimmunity, and immune suppression have been reported. Differences in the levels and functions of various cell types and components of both the innate and adaptive immune system supporting these changes have been described at (sub)acute and chronic stages post-injury. Further research is needed for a more comprehensive understanding of the peripheral immune reactions following SCI, their possible correlations with clinical characteristics, and how these immune responses could be targeted to facilitate the therapeutic management of SCI. In this review, we provide an overview of the current literature discussing changes in the peripheral immune system and their occurrence over time following a traumatic SCI.